Being a Catholic Religion Teacher: An Exciting Task! - Salas Ximelis, Antonio (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2020)
This paper aims to reveal the main characteristics that future Catholic religión teachers should embody, thus exposing the guidelines of the training required and how can Catholic religion teachers might eventually be declared competent from an academic point of view by the Catholic Church (DECA). Furthermore, we pretend to show future Catholic religion teachers what are the main personal traits expected to complete such exciting task. We have taken for granted that the subject of Catholic religion is offered as human right for both believers and non-believers, but grounded on the faith of the teachers in communion with the Church that sends them to carry out this task in a the specific context of the school. We encourage pre-service Catholic religion teachers to learn how to build bridges and break down walls. the paper finishes highlighting how exciting this task is and how worthy it is to get actively involved, thus dedicating their entire life to teaching Catholic religion.
Keywords: Catholic religion subject; Catholic religion teacher; DECA; training